K-theory for Cuntz-Krieger algebras arising from real quadratic maps - Nuno Martins; Ricardo Severino; J. Sousa Ramos (International Journal of Mathematics and Mathematical Sciences)
We compute the K-groups for the Cuntz-Krieger algebras 𝒪A𝒦(fμ), where A𝒦(fμ) is the Markov transition matrix arising from the kneading sequence 𝒦(fμ) of the one-parameter family of real quadratic maps fμ.